Implementasi Quick Response (QR) Code Pada Transaksi Pembayaran Dengan Enkripsi Message-Digest Algortihm 5 - Nugraha, Hary (Department of Informatics, Siliwangi University, Indonesia, 2021)
The rapid development of the times has made the community busy with various activities that collide with the limited time they have. This causes people to always look for ways to be able to carry out all the demands of these activities effectively and efficiently. Technological innovations such as electronic payment systems and virtual queues are one of the answers that can be used to help people carry out activities. The existence of this electronic payment system makes it easier for people to make payment transactions with this virtual queue which is a solution to solving queuing problems which usually take a long time, so that this virtual queue can help people to cut the time that is usually used to queue and allocate it for activities other.